Fusarium Endophthalmitis following Cataract Surgery: Successful Treatment with Intravitreal and Systemic Voriconazole - Paulo A. Alves da Costa Pertuiset; Juan F. Batlle Logroño (Case Reports in Ophthalmological Medicine)
Purpose. To report a case of postoperative endophthalmitis caused by Fusarium species successfully treated with intravitreal and systemic voriconazole after treatment failure with amphotericin B. Methods. Clinical case report of a 60-year-old immunocompetent woman who presents with endophthalmitis of unknown origin 4 weeks after uneventful cataract extraction and IOL implantation surgery. IOL explantation, vitrectomy with capsular bag removal, vitreous aspiration for culture, and intravitreal injection of amphotericin B (5 μg/0.1 mL) were performed. Diagnosis was established by culturing the vitreous aspirate on a Sabouraud agar medium and staining with lactophenol blue solution. Five days later, there was no clinical response. The decision was made to administer a single dose of intravitreal voriconazole (2.5 μg/0.1 mL) and oral voriconazole (200 mg BID) for 30 days. Results. Fusarium sp. grew on culture. Treatment with local and systemic voriconazole was started after no improvement with vitrectomy, IOL explantation, and intravitreal amphotericin B. After 1 month of treatment, the infection resolved and best-corrected visual acuity was 20/25. Conclusion. In patients with endophthalmitis caused by Fusarium sp., topical and systemic voriconazole treatment should be considered in cases resistant to intravitreal amphotericin B.